The Role of Non-Typeable Haemophilus influenzae Biofilms in Chronic Obstructive Pulmonary Disease - Weeks, Jake R.; Staples, Karl J.; Spalluto, C. Mirella; Watson, Alastair; Wilkinson, Tom M. A. (Frontiers in Cellular and Infection Microbiology, 2021)
Non-typeable Haemophilus influenzae (NTHi) is an ubiquitous commensal-turned-pathogen that colonises the respiratory mucosa in airways diseases including Chronic Obstructive Pulmonary Disease (COPD). COPD is a progressive inflammatory syndrome of the lungs, encompassing chronic bronchitis that is characterised by mucus hypersecretion and impaired mucociliary clearance and creates a static, protective, humid, and nutrient-rich environment, with dysregulated mucosal immunity; a favourable environment for NTHi colonisation. Several recent large COPD cohort studies have reported NTHi as a significant and recurrent aetiological pathogen in acute exacerbations of COPD. NTHi proliferation has been associated with increased hospitalisation, disease severity, morbidity and significant lung microbiome shifts. However, some cohorts with patients at different severities of COPD do not report that NTHi is a significant aetiological pathogen in their COPD patients, indicating other obligate pathogens including Moraxella catarrhalis, Streptococcus pneumoniae and Pseudomonas aeruginosa as the cause. NTHi is an ubiquitous organism across healthy non-smokers, healthy smokers and COPD patients from childhood to adulthood, but it currently remains unclear why NTHi becomes pathogenic in only some cohorts of COPD patients, and what behaviours, interactions and adaptations are driving this susceptibility. There is emerging evidence that biofilm-phase NTHi may play a significant role in COPD. NTHi displays many hallmarks of the biofilm lifestyle and expresses key biofilm formation-promoting genes. These include the autoinducer-mediated quorum sensing system, epithelial- and mucus-binding adhesins and expression of a protective, self-produced polymeric substance matrix. These NTHi biofilms exhibit extreme tolerance to antimicrobial treatments and the immune system as well as expressing synergistic interspecific interactions with other lung pathogens including S. pneumoniae and M. catarrhalis. Whilst the majority of our understanding surrounding NTHi as a biofilm arises from otitis media or in-vitro bacterial monoculture models, the role of NTHi biofilms in the COPD lung is now being studied. This review explores the evidence for the existence of NTHi biofilms and their impact in the COPD lung. Understanding the nature of chronic and recurrent NTHi infections in acute exacerbations of COPD could have important implications for clinical treatment and identification of novel bactericidal targets.